2022
DOI: 10.1073/pnas.2200058119
|View full text |Cite
|
Sign up to set email alerts
|

High conductivity Sepia melanin ink films for environmentally benign printed electronics

Abstract: Melanins (from the Greek μέλας, mélas, black) are bio-pigments ubiquitous in flora and fauna. Eumelanin is an insoluble brown–black type of melanin, found in vertebrates and invertebrates alike, among which Sepia (cuttlefish) is noteworthy. Sepia melanin is a type of bio-sourced eumelanin that can readily be extracted from the ink sac of cuttlefish. Eumelanin features broadband optical absorption, metal-binding affinity and antioxidative and radical-scavenging properties. It is a prototype of benign material f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…However, in those studies, no attention was drawn to a possible increase in their charge transport electronic component. Also, a recent study has shown that a natural sepia -NF-eumelanin can support such an IS behavior in a dried environment, 45 ascribed to the electronic component.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in those studies, no attention was drawn to a possible increase in their charge transport electronic component. Also, a recent study has shown that a natural sepia -NF-eumelanin can support such an IS behavior in a dried environment, 45 ascribed to the electronic component.…”
Section: Resultsmentioning
confidence: 96%
“…Nonetheless, shreds of evidence for an electronic component cannot be ignored entirely. 30,[42][43][44][45] Herein, we investigate the electrical properties of eumelanin by systematically evaluating its electrical current response in a biomimetic aqueous suspension (phosphate buffer saline, PBS, solution) under different pH levels. Electrical DC and voltage-dependent impedance/dielectric spectroscopy measurements are carried out on high-quality thin films.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Consequently, it was used as a gate material in a solid-state electrochemical transistor whose channel was made of PEDOT:PSS. 15,16 Other well-known areas of applied development exploit the properties of eumelanin as a photoacid, 17 use its ability to convert ionising radiation, 18 allow creating printed electronics using eumelanin-based conductive ink, 19 as well as various sensors and electrodes. 20 Many of these applications depend on the conductive properties of eumelanin, which are determined by the structure of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Sepia powder was extracted using a previously reported extraction protocol. 19,20 Briefly, 300 g of raw ink was suspended in 500 mL of HCl (2 M, Acros Organics). The suspension was stirred at room temperature for 24 hours, sequentially centrifuged (Allegra X-30R centrifuge, Beckman Coulter) and dispersed as follows: three times with HCl (0.5 M), once with de-ionized (DI) water, once with a buffer solution (0.02% v/v of monobasic sodium phosphate (200 mM, Sigma Aldrich), 32.49% v/v of dibasic sodium phosphate (200 mM, Sigma Aldrich) and 67.49% v/v of DI water), once with ethanol (Sigma Aldrich), once with DI water and finally once with ethyl acetate (Sigma Aldrich), for a total of 10 steps.…”
Section: Experimental Methodsmentioning
confidence: 99%